QUANTIFICATION OF TUNA FISH TARGET STRENGTH USING QUANTITATIVE ECHO SOUNDER - Henry M. Manik (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
A preliminary research programme was carried out in order to study the acoustic wave reflection or target strength (TS) of tuna fish using a quantitative echo sounder (QES). The relationships between TS to fork length (FL) and swimbladder volume, for bigeye tuna (Thunnus obesus) and yellowfin tuna (T. albacares) are investigated. The TS of bigeye tuna was about 3 dB higher than yellowfin tuna when comparing species at the same size. The result can be correlated to the swimbladder volume differencebetween species. The relationship between TS and swimbladder volume was quantified for both species.Keywords: tuna fish, target strength, quantitative echo sounder